Bali Area Political Situation of - Report on by W. E. Hunt Esquire (Colonial Letters and the Contact of Knowledges, 1921)
This file contains colonial letters on Bali Area and report by W. E. Hunt
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies